PENGARUH MOTIVASI INVESTASI, LITERASI KEUANGAN TERHADAP MINAT MAHASISWA INVESTASI DI PASAR MODAL - Siti Amrina Hasibuan; Boy Uli Kirana Situmorang; Azizul Hakim Nugraha; Fera Silvia; Purnama Ramadani Silalahi (Fakultas Teknik Universitas Maritim AMNI Semarang, 2022)
This study aims to determine the effect of investment motivation and financial literacy on investment interest. The method used through a quantitative approach. This study used a population of students from the Faculty of Economics and Islamic Business at the State Islamic University of North Sumatra class of 2019 with a sample of 51 students. The results show that partially the investment motivation variable has no effect on investment intention, while the financial literacy variable has a positive and significant relationship to investment interest. Simultaneously there is an influence between investment motivation and financial literacy variables on investment interest. Furthermore, the value of the coefficient of determination shows 74.7%